Switchable multiwavelength ytterbium-doped fiber laser using a non-adiabatic microfiber interferometer - Zulkhairi, A.S. (Interperiodica, 2017)
In this paper, we have successfully demonstrated a stable dual, triple and quad-wavelength generation of ytterbium-doped fiber by incorporating a non-adiabatic microfiber interferometer (N-MI) into the laser ring cavity. Three sets of dual-wavelength, two sets of triple-wavelength and one set of quad-wavelength with the same wavelength spacing of 4.24 nm for all sets of multiwavelengths over the range of 1035 nm to 1050 nm are obtained by means of a nonlinear polarization rotation mechanism. The side-mode suppression ratio (SMSR) is ∼53 dBm while the wavelength fluctuation and maximum power are 0.01 nm and less than 0.6 dB, respectively. Such features offer flexibility in multiwavelength generation and a stable output, with addition to a reliable system at an ambient temperature.